The Struggle of Hybrid Entepreneur in The New Normal Era - Ni Putu Sintha Devi Yogandhi; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2021)
This study aims to know and analyze about Hybrid Entrepreneur and the strategy of Hybrid Entrepreneur in the New Normal Era. The research setting is the physical environment with a qualitative approach. Key Informan is a Hybrid Entrepreneur determined by Purposive Sampling technique. Data collection was done by interviews, observations and documentation. The data source is from sources that can be used as a Hybrid Entrepreneur model and process by using Strategy Management approach with technical analysis of strategy formulation is based on a three-stage framework of strategy formulation with analysis tools Internal Factor Evaluation Matrix, External Factor Evaluation Matrix, Strengths-Weakness-Opportunities-Threats Matrix and the Quantitative Strategic Planning Matrix. The conclusion are to become a Hybrid Entrepreneur should be based on expertise, while also having the ability to take opportunities and the courage in making business decisions. Market Penetration Strategy is the most appropriate strategy in facing competition in this New Normal era with the best long-term strategy is Integration Strategy, which is to increase the sales network directly to consumers, then increase control over suppliers for product innovation development, and increase competitiveness among others by acquiring competitors.